Ответ: [tex]\infty.[/tex]
Пошаговое объяснение: [tex]{}[/tex]
[tex]\lim\limits_{n\to \infty}\left(\sqrt[3]{n^3+n^2}-\sqrt[3]{n^2-n}\right)=\lim\limits_{n\to \infty}n\left(\sqrt[3]{1+\frac{1}{n}}-\sqrt[3]{\frac{1}{n}-\frac{1}{n^2}}\right)=\infty(1-0)=\infty.[/tex]
Мы воспользовались тем, что [tex]\lim\limits_{n\to \infty}\dfrac{1}{n}=0.[/tex]
Copyright © 2025 SCHOLAR.TIPS - All rights reserved.
Answers & Comments
Ответ: [tex]\infty.[/tex]
Пошаговое объяснение: [tex]{}[/tex]
[tex]\lim\limits_{n\to \infty}\left(\sqrt[3]{n^3+n^2}-\sqrt[3]{n^2-n}\right)=\lim\limits_{n\to \infty}n\left(\sqrt[3]{1+\frac{1}{n}}-\sqrt[3]{\frac{1}{n}-\frac{1}{n^2}}\right)=\infty(1-0)=\infty.[/tex]
Мы воспользовались тем, что [tex]\lim\limits_{n\to \infty}\dfrac{1}{n}=0.[/tex]